2021
DOI: 10.3390/antibiotics10010086
|View full text |Cite
|
Sign up to set email alerts
|

Facile In-Situ Fabrication of a Ternary ZnO/TiO2/Ag Nanocomposite for Enhanced Bactericidal and Biocompatibility Properties

Abstract: This paper presents for the first time a successful fabrication of ternary ZnO/TiO2/Ag nanocomposites consisting of zinc oxide (ZnO), titania (TiO2) and silver (Ag) nanoparticles (NPs) synthesised using Morinda citrifolia fruit (MCF) extract. ZnONPs were synthesised using the co-precipitation method, and TiO2 and Ag were introduced into the precursor solutions under microwave irradiation to obtain ZnO/TiO2/Ag nanocomposites (NCs). This material demonstrated enhanced bactericidal effect towards bacterial pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
(60 reference statements)
1
2
0
Order By: Relevance
“…The living (control) cells fluoresced green due to the diffusion of AO into the cellular membranes, but the treated cells turned apoptotic and fluoresced orange due to nuclear shrinkage. An earlier study conducted with ZnO/TiO 2 /Ag NCs also revealed similar observations [ 47 ]. The chromatin fragmentation that occurred in the NCs-treated cells indicated an uptake of EtBr dye, as observed with chitosan decorated silver nanoparticles in an earlier report [ 48 ].…”
Section: Discussionsupporting
confidence: 77%
“…The living (control) cells fluoresced green due to the diffusion of AO into the cellular membranes, but the treated cells turned apoptotic and fluoresced orange due to nuclear shrinkage. An earlier study conducted with ZnO/TiO 2 /Ag NCs also revealed similar observations [ 47 ]. The chromatin fragmentation that occurred in the NCs-treated cells indicated an uptake of EtBr dye, as observed with chitosan decorated silver nanoparticles in an earlier report [ 48 ].…”
Section: Discussionsupporting
confidence: 77%
“…8a and b ), as shown in the previous study. 56 It can be seen in Fig. 8a and b that the cell viability was highly decreased for ZnO-TiO 2 NC due to the addition of the ZnO sheet due to their increasing surface charges.…”
Section: Resultsmentioning
confidence: 90%
“…Finally, the presence of both hydrophilic and hydrophobic groups allows amphiphilic chitosan to self-assemble into micelles, which can enhance its solubility and bioavailability, as well as provide a means for the targeted delivery of the antimicrobial agent [52,53]. S2, Supplementary Materials) [61][62][63][64]. However, the newly synthesized PIACSB-coated TiO 2 -ZnO nanocomposite is particularly exciting due to its amazing antimicrobial activity (MIC/MBC→0.34/0.68 µg/mL, 0.20/0.40 µg/mL, and 0.15/0.30 µg/mL against S. aureus, E. coli, and P. aeruginosa, respectively) and unique properties.…”
Section: Proposed Molecular Mechanisms Of Antimicrobial and Antibiofi...mentioning
confidence: 99%